Attitudes and Preferences of Self-Repair and Corrective Feedback of Oral Production in Classroom: A Corpus-Based Study The case of Second Year LMD students at the University of “Frères Mentouri” Constantine - AOUICHE, Fahima (Journal of Human Sciences, 2017)
Oral errors are commonplace in the EFL learning process. The willingness to elicit teachers’ and students’ collaboration in error treatment towards enhancing oral production and uptake is the aim behind this study. Based on the main questions “Who, when, what and how to correct?” and “How much uptake is generated?”, two attitudinal questionnaires were delivered to 150 second year LMD students and 16 teachers in the English department inquiring their perceptions about error repair. We further probed both teachers’ and students’ repair behaviour via a non-participatory natural classroom observation during 16 hours of oral courses varied between interaction and presentations. We detected controversial, though not conflicting, results on two levels of analysis: Students’ Vs Teachers’ attitudes and preferences towards the repair of oral failures, besides the claimed attitudes Vs those revealed during classroom observation which generated average amounts of students’ uptake. These findings lend a strong support for our hypothesis, which speculates that the betterment of students’ spoken language can be achieved through a conscious cooperation between teachers and students regarding each others’ preferences towards error treatment. Those preferences are worthy of further pursuit of research.